Inspiring a generation: an examination of stakeholder relations in the context of London 2012 Olympics and Paralympics educational programmes. Issue 4 (2nd November 2018) - Postlethwaite, Verity; Kohe, Geoffery Z.; Molnar, Gyozo
ABSTRACT: The London 2012 Olympic and Paralympic Games (London 2012) inspire a generation legacy aim targeted young people in the United Kingdom (UK) and internationally. This article explores how the London 2012 education-based legacy programmes aimed at young people, such as the Get Set initiative, affected relations between stakeholders connected to the Games. Utilising a stakeholder relations theoretical perspective we analysed documentary-based dialogue from a UK parliament Education Committee inquiry through a critical discourse analysis. From the analysis two discourses emerged. Firstly, around clarity of the purpose of the London 2012 educational programmes. Secondly, varying stakeholders' understanding during the inquiry of the inspire a generation legacy aim was articulated around the notion of a "missed opportunity, " in particular, when translated into the domestic policy context around education and sport. The findings encourage stakeholders to reflect on potential fragmented accountability between sport mega event and domestic sectors; and achieving greater clarity to the purpose of legacy-based educational programme within a broader policy context.